Reproducción de Oenomaus ortignus (Lepidoptera: Lycaenidae) en Barva, Heredia, Costa Rica - Calvo, Renán (Universidad de Costa Rica, 1998)
A group of Almona cherimolia (Mill:Annonaceae) trees was studied in Barva, Heredia, Costa Rica (June 1991- August ¡ 992) to record egg-Iaying sites of the butterfIy Oenomaus ortignus (Lepidoptera: Lycaenidae). Used fruits often dehydrated and fell before maturity. Eggs are laid in fruits independently of fruit ontologic state and of height above ground. Tree parts les s frequently used to lay eggs are fIower primordia, leaves and stems, but the larvae move to fruits when rood reserves are depleted. Pupation occurs outside the fruit. Pupae emit sound, possible for defence.